Bovine cyclic GMP-AMP synthase recognizes exogenous double-stranded DNA and activates the STING-depended interferon β production pathway. (February 2023) - Dai, Haiyue; Wang, Yixiao; Fan, Zhenying; Guo, Yongli; Chen, Jiaqi; Meng, Ye; Tong, Xin; Gao, Mingchun; Wang, Junwei
Abstract: The cytosolic DNA sensor cyclic GMP-AMP synthase (cGAS) recognizes exogenous double-stranded DNA and produces 2′3′-cyclic GMP-AMP (2′3′-cGAMP), activating the stimulator of interferon genes (STING) and innate immunity. Bovine cGAS functions remain poorly understood. Herein, the coding sequence of the bo-cGAS gene was obtained and its recognition function was investigated. Bo-cGAS consists of 1542 nucleotides and the encoding acid sequence contained high sequence homology to that of other livestock. Bo-cGAS was localized in the endoplasmic reticulum and was abundant in the lung. Bo-cGAS and bo-STING coexistence significantly activated the IFN-β promotor. Synthesized 2′3′-cGAMP activated the STING-dependent pathway. Upon bo-cGAS recognition of poly(dA:dT) and bovine herpesvirus type 1 (BHV-1), Viperin transcription displayed the opposite time-dependent trend. Significant restriction of IFN-β transcription but augmentation of myxovirus resistance protein 1 (Mx1) and Viperin occurred during BHV-1 infection. Thus, bo-cGAS recognized exogenous double-stranded DNA and triggered the STING-dependent IFN-β production pathway. Highlights: The coding sequence of the cGAS gene was obtained in bovine. Bo-cGAS expressed at the endoplasmic reticulum and abounded in the lung. Bo-cGAS and bo-STING co-existence significantly activated the IFN-β promotor. Bo-cGAS could recognize the exogenous DNA and trigger the STING-dependent IFN-β production pathway.